Synthesis, Crystal Structure, and Hirshfeld Surface Analysis of Hexachloroplatinate and Tetraclorouranylate of 3-Carboxypyridinium—Halogen Bonds and π-Interactions vs. Hydrogen Bonds - Anton Petrovich Novikov; Mikhail Alexandrovich Volkov; Alexey Vladimirovich Safonov; Mikhail Semenovich Grigoriev (Crystals, 2022)
This work aimed to synthesize new platinum and uranium compounds with nicotinic acid. In this article we describe the synthesis of two new anionic complexes (HNic)2[PtCl6] and (HNic)2[UO2Cl4] using wet chemistry methods. The structure of the obtained single crystals was established by single-crystal X-ray diffraction. The Hirshfeld surface analysis of the obtained complexes and their analogue (HNic)2[SiF6] was carried out for the analysis of intermolecular interactions. Hydrogen bonds (H···Hal/Hal···H and O···H/H···O) make the main contribution to intermolecular interactions in all compounds. Other important contacts in cations in all compounds are H···H, C···H/H···C and C···Hal/Hal···C; in anions H···Hal/Hal···H. The Pt-containing complex has a halogen-π interaction and halogen bonds, but Si-containing complex has a π–π staking interaction; these types of interactions are not observed in the U-containing compound.